(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A riddle that time and again faced by politicians and social reformers is as how to raise the social and civic status of people belonging to Scheduled Castes. The cares of Scheduled castes people were put to front in Bengal by Raja Ram Mohan Roy, Swami Dayanand served their cause in North India and Dr. Annie Besant and Col. Olcott handled the south for bringing some kind of positive energy and hopes in the feeble minds of Scheduled Caste people, that had been feebled by generations of oppressions and depressions. The movement like Arya Samaj, Theosophical society, The Brahma Samaj were exceptionally great movement which brought reformation among Scheduled Castes and mitigated their sufferings. Some legislation for the upliftment of these socially thrown people were adopted and implemented but no serious contemplation was given to eradicating the root cause i.e. castiesm, the evil.